(3YOI GdMUf GdMUjf ef cdGe SjO GdeQSdjfs - (3eMeO Hf eMeO Hf eMeO Hf Ydj Hf jhSa, CHh GdNjQ, TeS GdOjf, GdYeQj GdOeTbqj Ke GdTjQGRj GdTGaYqj, GdTgjQ HGHf GdLRQj , (B833 (3g` s ((3aJM Hf SjO Ydjs)
(3ChdgG (B:s
(3bGdeMeO Hf eMeO Hf eMeO GHf GdLRQjGdMeO ddg GdPj LYd PcQg ef GdMUf GdMUjfCeG HYO adeG cGf cJGH GdMUf GdMUjf MOGfj Ydi GNJUGQg aj gPg GdChQGbs
(3BNQgG (B:s
(3hYQV eG Hjf GdfaS hGdghi hGdTjWGf ceG hQO aj GdNHQ Gddge EfG fSCdc GdYah hGdYGajI aj GdOjf hGdOfjG hGdBNQIs
(3aj BNQg aGFOI ddTjNGf ef MGTjI GdcaGjI aj Gdabg GdTGaYj hef aJGhi GHf MLQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 7 / 45s
(3eYLe GdeDdajf(B: 3 / 687s
(3cTa GdXfhf(B: 1 / 670s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs